PENINGKATAN KUALITAS PAKAN AYAM DENGAN PENAMBAHAN ENZIM : Pengaruh enzim terhadap nilai daya cerna, neraca nitrogen dan neraca energi. - Patuan L.P. Siagian (Research Center for Chemistry - LIPI, 1998)
In order to improve the feed quality, enzyme preparatories were added to the diets, wich all of the main components were plant origin. Five treatments in a completely randomized design were 9 fold replicaed, namely: 1. Diet without enzyme addition (control), 2. (-glucanose added to the diet), 3. Hemicellulase added to the diet, 4. Cellulase added to the diet, 5. (-glucanase, hemicellulase and cellulase added to the diet. To ascertain the digestibility of the nutrients of the treated diets, a total of 90 male chicks of LSLBrown were selected and kept in a climate conditioned room (temperature 22 °C, relative humidity 65-70 %, lighting 24 hours per day of 20-25 Lux).The results of this experiment showed that the addition of the enzyme to the diet effected Significantly the digestibility of the fat (p 0,001),ash (p . 0,05) and sugar (p 0,05). The addition of combined (-glucanase, hemicellul ase, and cellulase to the diet improved feed conversion ratio of 9, 7 % compared to the control. The nitrogen effictenoy ratio and anergi efficiency ratio were also significantly better (p O,05), each of 9.8 % and ll.8 %.